Research handbook on human rights and the environment - Grear, Anna, 1959-; e (Cheltenham, UK : Edward Elgar Publishing, 2015)
Bringing together leading international scholars in the field, this authoritative Handbook combines critical and doctrinal scholarship to illuminate some of the challenging tensions in the legal relationships between humans and the environment, and human rights and environment law. The accomplished contributors provide researchers and students with a rich source of reflection and engagement with the topic. Split into five parts, the book covers epistemologies, core values and closures, constitutionalisms, universalisms and regionalisms, with a final concluding section exploring major challenges and alternative futures. An essential resource for students and scholars of human rights law, the volume will also be of significant interest to those in the fields of environmental and constitutional law.
Epistemologies of mastery / Sam Adelman -- Epistemologies of doubt / Andreas Philippopoulos-Mihalopoulos -- Ecological subjectivities, responsibilities, and agency / Lorraine Code -- Environmental human rights: a constructive critique / Peter D. Burdon -- The closures of legal subjectivity: why examining 'law's person' is critical to an understanding of injustice in an age of climate crisis / Anna Grear -- Property rights, environmental justice and worldly order -- lessons from natural law / Sean Coyle -- Re-imagining the role of the sovereign state and individual rights in mitigating the effects of the deterioration of the environment / Francois Venter -- Human rights and the environment through an environmental constitutionalism lens / t Aligning international environmental governance with the 'Aarhus principles' and participatory human rights / Ulrich Beyerlin -- The interaction between human rights and the environment in the European 'Aarhus space' / Ellen Hey -- International courts and environmental human rights: re-imagining adjudicative paradigms / Evadne Grant -- Human rights and the environment in the African Union context / Werner Scholtz -- Protecting the human rights of climate displaced persons: the promise and limits of the United Nations Framework Convention on Climate Change / Rosemary Lyster -- Human rights, environmental justice, and the North-South divide / Carmen G. Gonzalez -- Selectivity in law-making: regulating extraterritorial environmental harm and human rights violations by transnational extractive corporations / Penelope Simons -- Ecosystem services, fear and the subjects of environmental human rights / Afshin Akhtar Khavari -- Environmental and human rights in ethical context / Klaus Bosselmann.
Includes bibliographical references and index.
Keywords: Environmental law, International; Human rights; 86.75 environmental law; 86.81 human rights; Environmental law, International; Human rights; Umweltethik; Legal Canadiana